PERAN ARTIFICIAL INTELLIGENCE DALAM MENGURANGI PERILAKU KORUPTIF: (Perspektif Pendidikan Islam) - Ainurrafiq Dawam; Muhammad Adwim Rifqy El-Hisan (Prodi Magister Pendidikan Agama Islam (MPAI) - STAI Nida El-Adabi Bogor, 2024)
This study explores the potential role of Artificial Intelligence (AI) in reducing corrupt behavior, focusing on the perspective of Islamic Education. Corruption is a global issue that hinders development and undermines public trust in government institutions. In Indonesia, despite anti-corruption efforts, the Corruption Perception Index remains low, indicating the need for innovative new approaches. AI, with its complex data analysis capabilities, can be an effective tool in detecting and preventing corruption, including identifying suspicious transaction patterns and conflicts of interest. Additionally, Islamic education, which emphasizes values such as honesty and justice, has great potential in shaping anti-corruption character. The integration of AI with Islamic education could create a more effective approach to reducing corrupt behavior, especially among the younger generation. However, the implementation of AI in this context also faces challenges, including privacy issues, algorithmic bias, and the digital divide. This study emphasizes the importance of a holistic approach involving collaboration between the government, academics, and civil society to maximize AI's potential in combating corruption. AI implementation must be aligned with Islamic principles, ensuring that this technology is used ethically and in accordance with moral values. The study concludes that while AI is not a standalone solution to corruption, it can be an important part of a broader anti-corruption strategy when applied wisely and ethically.